عقد الإيجار التمويلي كآلية لتمويل المؤسسات الصغيرة والمتوسطة في القانون الجزائري - نادية، لاكلي (جامعة زيان عاشور بالجلفة, 2023)
تلعب المؤسسات المتوسطة والصغيرة في وقتنا الراهن دورا فعالا في تنمية الاقتصاد الوطني في مختلف المجالات وتحاول معظم الدول النامية ترقية وتطوير هذه المؤسسات لتنشيطها وتحقيق فعاليتها، ويشكل الجانب التمويلي أهم وسيلة لدعم هذه المؤسسات. ورغم تعدد صيغ التمويل إلا أنا تفضل المؤسسات المتوسطة والصغيرة اللجوء الإيجار التمويلي بشتى أنواعه باعتباره الوسيلة الأكثر ملاءمة لطبيعتها وحجمها، وتهدف هذه الدراسة إلى تحديد مفهوم المؤسسات المتوسطة والصغيرة في التشريع الجزائري من جهة، والتعرف على الإيجار التمويلي وصوره في القانون الجزائري. وتأسيسا لما سبق، سنتطرق في المحور الأول من هذه الدراسة إلى الإطار المفاهيمي للمؤسسات المتوسطة والصغيرة من خلال التعرف على ماهيتها والشروط المتعلقة بها، بينما سنتعرف في المحور الثاني على مفهوم الإيجار التمويلي وصوره. At present, small and medium-sized enterprises play an active role in the development of the national economy various fields. Most developing countries are trying to promote and develop these institutions in order to stimulate them and achieve their effectiveness. The financing aspect is the most important means to support these institutions. Despite the many forms of financing, small and medium-sized enterprises prefer to resort to financial rentals of all types as the most appropriate means for their nature and size. The study aims to define the concept of small and medium-sized enterprise in Algerian legislation and to identify financial rents and their images in Algerian law. Based on the foregoing, we will address the conceptual framework of SMEs in the first section of this study by identifying their terms and conditions, while the concept and concept of financial lease will be defined in the second section.
Keywords: التأجير التمويلي -- تقنيات البنوك -- الدول النامية -- القانون الجزائري